Kajian Yuridis Dasar Hukum Jaksa Penuntut Umum Melakukan Upaya Hukum Kasasi Terhadap Putusan Bebas (Vrijspraak) Dalam Sistem Peradilan Pidana Indonesia - Heru Drajat Sulistyo (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2019)
This study discusses theoretically normative about the appeal made by the Public Prosecutor on the verdict free (vrijspraak) in the Indonesian Criminal Justice System intended to find solutions to the juridical problems arising from the acquittal. The problem in this study, namely: What is the legal basis for the Public Prosecutor to conduct an appeal against the verdict (vrijspraak). The research method used is a normative legal research method and uses secondary data types, including primary legal materials, secondary legal materials and tertiary legal materials collected through library studies, print media, electronic media. The results of the research study, namely: the legal basis of the Public Prosecutor conducting an appeal against the verdict (vrijspraak) is the Decree of the Minister of Justice of the Republic of Indonesia Number M.14-PW.07.03 of 1983 dated December 10, 1983 concerning Supplementary Guidelines for the Implementation of the Criminal Procedure Code (item 19) . Then the Supreme Court Decree Reg. no: 275 K / Pid / 1983 in the Raden Sonson Natalegawa case was the first decision to be born as jurisprudence for a free verdict after the entry into force of the Criminal Procedure Code. Furthermore, the Constitutional Court Decision Number 114 / PUU-X / 2012 dated March 28, 2013. The existence of the Constitutional Court Decision Number 114 / PUU-X / 2012 dated March 28, 2013, the public must accept the Public Prosecutor is contested with legal action to appeal against the acquittal (vrijspraak).